Legal Policy Establishment of Article 107 Numbers 2 Law Number 11 of 2020 on Job Creation Reviewed From Transfer Of Technology Regulation in Article 7 Trade Related Aspects of Intellectual Property Rights (TRIPs) - Dian Ayu Nurul Muthoharoh; Yuliati Yuliati; Afifah Kusumadara (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The purpose of this study is to analyze the Legal Policy Establishment of Article 107 Numbers 2 Law Number 11 of 2020 on Job Creation Reviewed From Transfer of Technology Regulation in Article 7 TRIPs. This research is normative legal research by prioritizing statutory approaches and historical approach. The results of the study show that Article 107 Numbers 2 Law Number 11 of 2020 on Job Creation is not by the mandate of Article 7 TRIPs, and implicated for the absence of government interference in technology transfer especially in the field of patents. The legal policy of establishing Article 107 Numbers 2 Law Number 11 of 2020 on Job Creation is influenced by the intervention of other countries and more inclined towards adjusting international trade politics than defending national interests. The most ideal arrangement regarding technology transfer is by the formulation of Article 20 Paragraph (2) Law Number 13 of 2016 concerning Patents, which in essence patents must support technology transfer. Suggestions in this study for the lawmaker should emphasize the necessity for technology transfer in the field of patents through licenses in Indonesian laws and regulations.